2009
DOI: 10.1038/emboj.2009.244
|View full text |Cite
|
Sign up to set email alerts
|

Editing independent effects of ADARs on the miRNA/siRNA pathways

Abstract: Adenosine deaminases acting on RNA (ADARs) are best known for altering the coding sequences of mRNA through RNA editing, as in the GluR-B Q/R site. ADARs have also been shown to affect RNA interference (RNAi) and microRNA processing by deamination of specific adenosines to inosine. Here, we show that ADAR proteins can affect RNA processing independently of their enzymatic activity. We show that ADAR2 can modulate the processing of mir-376a2 independently of catalytic RNA editing activity. In addition, in a Dro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
181
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(194 citation statements)
references
References 55 publications
13
181
0
Order By: Relevance
“…Our data revealed that RNA editing has little correlation with mRNA expression changes in ADAR1 KD H9 cells (Supplementary information, Figure S4 and data not shown), which is in consistency with recent reports in other organisms [18][19][20]. We hypothesized that ADAR1 deficiency may lead to an altered miRNA repertoire, which in turn regulates mRNA expression in H9 cells and during differentiation.…”
Section: Adar1 Knockdown Dramatically Alters Mirna Repertoiressupporting
confidence: 91%
See 1 more Smart Citation
“…Our data revealed that RNA editing has little correlation with mRNA expression changes in ADAR1 KD H9 cells (Supplementary information, Figure S4 and data not shown), which is in consistency with recent reports in other organisms [18][19][20]. We hypothesized that ADAR1 deficiency may lead to an altered miRNA repertoire, which in turn regulates mRNA expression in H9 cells and during differentiation.…”
Section: Adar1 Knockdown Dramatically Alters Mirna Repertoiressupporting
confidence: 91%
“…Besides the catalytic activity of ADARs on miRNAs, it has been shown that ADARs can modulate the miR-NA/siRNA pathways independently of the editing activity in fly [19]. ADARs are also important for maintaining many small RNAs in C. elegans through both editing and non-editing activities [20].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that catalytically inactive ADAR1 and ADAR2 can modulate the micro RNA and siRNA pathways in Drosophila. 32 Similar functions might be expected for the inactive ADAR homologues in mammals. Catalytically inactive proteins might influence alternative splicing, hnRNA packaging or mRNA transport by their ability to bind dsRNA.…”
Section: Targets For Adenosine To Inosine Editingmentioning
confidence: 58%
“…Drosha cleavage of pri-mR-376a2 was inhibited by catalytically inactive ADAR2 because of ADAR2 binding [103]. This result indicates that other dsRNA binding proteins may bind to the pri-miRNA or pre-miRNA hairpin structures and affect the miRNA processing.…”
Section: Editing In Small Non-coding Rnasmentioning
confidence: 94%